TEACHERS’AND LEARNERS’ PERCEPTION OF THE SKILLS INTEGRATION IN THE FIRST YEAR SECONDARY SCHOOL COURSEBOOK “AT THE CROSSROADS” - ZINE, AMEL (My University, 2019)
ABSTRACT The purpose of this study is to explore the integration of the four skills in the coursebook “At the Crossroads” published by Algerian Education Ministry (AEM). Differing from the previous studies on the same coursebook, this study tries to find out whether there is integrated skill bias in the coursebook, although it is prepared with the claim that it is integrating the four skills and aiming to develop all of the four skills equally. In order to fulfill this aim, a student questionnaire and a teacher questionnaire, which aim to define the students and the teachers’ opinion on the effectiveness of the coursebook in terms of four skills, have been developed and submitted to First Year Secondary Education Students in Houari Boumedien High School in Berhoum and English Teachers in M’sila Secondary Schools. The findings of this research indicate the dissatisfaction of both students and teacher with the coursebook in terms of the efficacy of it in bettering students’ four skills. In addition, the results reveal that “At the Crossroads” is a reading dominant or reading biased coursebook in terms of skills integration.
Keywords: Keywords: At the Crossroads, integration, four skills